The clinical value of α-hydroxybutyrate dehydrogenase, cardiac troponin I, and B-type natriuretic peptide in perioperative diagnosis of heart failure in children with congenital heart disease - Yin, Jun; Wang, Qingsong; Xu, Shuqiong; Wang, Junru; Huang, Shihua; Shen, Junhong; Yuan, Tao; Luo, Tongyong; Wang, Xianmin (Frontiers in Pediatrics, 2025)
ObjectiveThis study evaluates the clinical value of α-Hydroxybutyrate Dehydrogenase (α-HBDH), Cardiac Troponin I (cTnI), and B-Type Natriuretic Peptide (BNP) in the perioperative diagnosis of heart failure in children with congenital heart disease (CHD).MethodsA retrospective analysis was performed on data from 107 children with CHD who underwent surgery between March 2022 and March 2023. Patients were categorized based on the European Society of Cardiology (ESC) cardiac function grading into three groups (Grades I–III) and further into heart failure (HF) and non-HF groups. Preoperative and postoperative levels of α-HBDH, cTnI, and BNP were compared across cardiac function grades and HF status. The diagnostic value of these biomarkers was assessed using receiver operating characteristic (ROC) curve analysis.ResultsPreoperative levels of α-HBDH, cTnI, and BNP were significantly higher in the HF group than in the non-HF group (all P < 0.05). These markers also increased with cardiac function severity, being highest in Grade III. Postoperatively, α-HBDH, CKMB, and BNP remained elevated in severe cases, correlating with worsening function (all P < 0.05). The ROC analysis showed that among the preoperative cardiac biomarkers in children with CHD, whether assessed individually or in combination, the combined detection of cTnI and BNP exhibited the highest diagnostic value for perioperative heart failure, with an AUC of 0.883.ConclusionIn children with CHD, preoperative levels of α-HBDH, cTnI, and BNP during the perioperative period are closely correlated with cardiac function, significantly increasing with the severity of cardiac dysfunction. These biomarkers have important clinical value for diagnosing heart failure, with the combined detection of cTnI and BNP demonstrating the highest diagnostic efficacy.